2012
DOI: 10.1073/pnas.1110203109
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modeling of respiratory syncytial virus infection of pediatric bronchial epithelium, the primary target of infection in vivo

Abstract: Respiratory syncytial virus (RSV) is the major viral cause of severe pulmonary disease in young infants worldwide. However, the mechanisms by which RSV causes disease in humans remain poorly understood. To help bridge this gap, we developed an ex vivo/in vitro model of RSV infection based on well-differentiated primary pediatric bronchial epithelial cells (WD-PBECs), the primary targets of RSV infection in vivo. Our RSV/WD-PBEC model demonstrated remarkable similarities to hallmarks of RSV infection in infant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
217
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(260 citation statements)
references
References 41 publications
36
217
3
Order By: Relevance
“…Previous studies have shown that RSV infects ciliated and bronchiolar airway epithelial cells in the respiratory tract, 34-36 as well as type II pneumocytes 37 38 Consistent with these findings, viral antigen expression was present on these cell types in the hRSV-infected lambs, with a significant correlation between hRSV expression in alveoli and bronchioles (Figure 8a).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown that RSV infects ciliated and bronchiolar airway epithelial cells in the respiratory tract, 34-36 as well as type II pneumocytes 37 38 Consistent with these findings, viral antigen expression was present on these cell types in the hRSV-infected lambs, with a significant correlation between hRSV expression in alveoli and bronchioles (Figure 8a).…”
Section: Discussionsupporting
confidence: 76%
“…Our study also confirms the previous suggestion that ciliated cells are the target of RSV infection [2,3]. Our study collected evidence using electron and confocal microscopy from RSV-infected and uninfected ciliated epithelium.…”
Section: Basal Cell Cultures Infected With Rsv Increase Secretion Of supporting
confidence: 79%
“…Recent evidence suggests that the virus initiates infection by targeting human ciliated epithelium lining the nasopharynx [2][3][4]. We have previously shown that nasal brush biopsies from hospitalised infants with bronchiolitis exhibited significant disruption of the ciliated epithelium during RSV infection, with recovery taking many weeks [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among these are three surface glycoproteins, the G glycoprotein, the F protein, and the small hydrophobic (SH) protein (1). The G protein is responsible for attachment with host cells, which are predominantly ciliated airway epithelial cells (7,8). Fusion of the viral and cellular membranes is facilitated by the RSV F protein, as is fusion between the membranes of infected cells with adjacent cells, which result in large, multinucleated syncytia.…”
mentioning
confidence: 99%